The Birth of the Modern Apple - Juniper, Barrie (Petits Propos Culinaires, 2025)
Alumni of Oxford suffer regular doses of fund-raising in the guise of Oxford Today: The University Magazine. Of late, it has improved greatly, with articles anyone might want to read. In the Michaelmas issue was this report by Dr Barrie juniper, Leverhulme Post-Retirement Emeritus Fellow in the Department of Plant Sciences and Fellow of St Catherine’s College. Presuming that not all PPC subscribers are from Oxford, noting that the piece had otherwise been seen only by visitors to St Catherine’s website, I thought it worth repeating here. I am grateful to Dr Juniper as well as to the Editor of Oxford Today for their permission.